A simple view of linguistic complexity. (January 2015) - Pallotti, Gabriele
Although a growing number of second language acquisition (SLA) studies take linguistic complexity as a dependent variable, the term is still poorly defined and often used with different meanings, thus posing serious problems for research synthesis and knowledge accumulation. This article proposes a simple, coherent view of the construct, which is defined in a purely structural way, i.e. the complexity directly arising from the number of linguistic elements and their interrelationships. Issues of cognitive cost (difficulty) or developmental dynamics (acquisition) are explicitly excluded from this theoretical definition and its operationalization. The article discusses how the complexity of an interlanguage system can be assessed based on the limited samples with which SLA researchers usually work. For the areas of morphology, syntax and the lexicon, some measures are proposed that are coherent with the purely structural view advocated, and issues related to their operationalization are critically scrutinized.